Male hormonal contraception: looking back and moving forward. (9th October 2015) - Roth, M. Y.; Page, S. T.; Bremner, W. J.
Summary: Despite numerous contraceptive options available to women, approximately half of all pregnancies in the United States and worldwide are unplanned. Women and men support the development of reversible male contraception strategies, but none have been brought to market. Herein we review the physiologic basis for male hormonal contraception, the history of male hormonal contraception development, currents agents in development as well as the potential risks and benefits of male hormonal contraception for men.